Designing and Creating an Automatic Hydroponic Plant Watering Control System Using a TDS Sensor Based on an ATMEGA328 Microcontroller - Hakim, Feriandanu; Supardi, I Wayan; Ratini, Ni Nyoman (BULETIN FISIKA, 2024)
In this research, an automatic hydroponic watering system has been designed and made using a total dissolved solid (TDS) sensor based on the ATmega328 microcontroller. The microcontroller contained in the Arduino Uno module functions as a design regulator. This research aims to assist in providing nutrition automatically so that it can help human work. The calibration results show that the tool designed has a good level of accuracy with the accuracy of the tool being 99.99%. These results show that the tool made can be used and runs well.